Delirium in the course of alcohol withdrawal syndrome complicated by rhabdomyolysis - Martyniuk, Agnieszka; Papuć, Ewa; Rejdak, Konrad; Stelmasiak, Zbigniew (Current Problems of Psychiatry, 2012)
Rhabdomyolysis is characterized by the leakage of contents of muscle cells including myoglobin, creatine kinase, alanine amino-transferase and aspartate aminotransferase into the circulation. Some of these sarcoplasmic proteins, such as the myoglobin, can be directly toxic to kidney cells and it can impair and clog the filtration system of the kidney. Both mechanisms can lead to kidney failure. The most common reported causes of rhabdomyolisis are physical factors like crush injury, strenuous exercise, extensive burns, high-voltage electrical injury, status asthmaticus, tetanus, prolonged seizures or status epilepticus, acute psychosis, alcohol withdrawal syndrome. Some people have a genetic susceptibility which increases the risk of rhabdomyolysis. We present a case of 35-year-old man with rhabdomyolisis caused by psychomotor agitation directly connected with delirium caused by alcohol withdrawal. The initial symptom was the characteristic reddish-brown discoloration of the urine as a result of myoglobinuria, with concomitant increased level of myoglobin and creatine kinase (CK) in the blood. The serum myoglobin concentration increased to 3300 ng/ml, and the creatine kinase was 182000,0 U/L. An improvement of patient’s state was observed after early fluid therapy which prevented acute renal failure.